Examining Experiences of Poor Sleep During Pregnancy: A Qualitative Study to Inform the Development of a Prenatal Sleep Intervention. (16th March 2022) - Felder, Jennifer N.; Mirchandaney, Riya; Harrison, Jessica; Manber, Rachel; Cuneo, Judith; Krystal, Andrew; Epel, Elissa; Hecht, Frederick
Background: Poor sleep is common during pregnancy and is associated with increased risk of negative health outcomes. Research indicates that physical discomfort and having an active mind are primary factors for prenatal sleep disturbances. Mindfulness-based interventions have the potential for addressing these factors, but have yet to be optimized for this purpose in this population. Objective: The objective of this study was to gather input from pregnant and postpartum individuals about the value of a mindfulness-based program for improving prenatal sleep and their preferred content and delivery format. Methods: We conducted 2 focus groups with 12 pregnant people experiencing poor sleep quality and 3 individual interviews with postpartum people. Interviews were thematically analyzed. Results: The majority of participants expressed strong interest in a mindfulness program for improving prenatal sleep. Participants reported that pregnancy-specific physical discomfort and worry (both general and pregnancy-specific) affected their sleep. Participants wanted sleep education, and strategies for calming the mind, reducing physical discomfort, reducing impact of bedtime partners on sleep, and tips for improving sleep schedule and quality. Participants recognized the convenience of an online intervention and the social benefits of an in-person intervention and favored a hybrid delivery model. Conclusion: Addressing prenatal sleep problems is an unmet need. Given the challenges and discomfort women face during pregnancy, and the importance of adequate sleep for promoting mental and physical health during pregnancy, sleep difficulties are critical to address. A mindfulness-based intervention for improving prenatal sleep was deemed of high interest to this perinatal population.